The Requirement of the Text for Fundamentalists and Its Applications in Jordanian Civil Law - Al-Saleh, Abdullah; Al-Issa, Hareth (Dirasat: Shari'a and Law Sciences, 2021)
Devising judgments from legal texts needs to be aware of fundamentalist rules for the existence of similarities between legal texts and legislative texts in that the legislative texts, including public, private, absolute, restricted and indicative of the phrase and with reference and as required and others and these are also present in the legal texts. This research shows the close relationship between the principles of jurisprudence and the Jordanian civil law by listing legal applications on the necessity of the text for fundamentalists. The study adopted the inductive method in order to extrapolate the meaning of the requirement of the text for fundamentalists and the legislator; extrapolating the statements of jurists from their various books. It also adopted the comparative method by comparing the opinions of jurists that need editing, and attributing them to their authors. The study concluded that the requirement is one of the ways to indicate the meaning of the two principles in proving the practical sharia rulings and that the requirement is either operative, understandable, or it is a part of them. The study recommended that science students should be directed to extract applications of semantics in Jordanian civil law in all its branches and compare them with Islamic jurisprudence.